Natural History of Aortic Regurgitation following Percutaneous Mitral Valvuloplasty - Sadr-Ameli, Mohammadali (Res Cardiovasc Med, 2013)
BACKGROUND: Little is known about the natural history of aortic regurgitation (AR) in patients undergoing mitral valve procedures for mitral stenosis. OBJECTIVES: The aim of this study was to evaluate the short- and long-term effects of percutaneous mitral valvuloplasty (PMV) on coexisting AR. MATERIALS AND METHODS: A total of 327 patients with rheumatic mitral stenosis (282 females and 45 males; mean age at the time of intervention = 47 ± 11 years) were followed up for between 48 hours and 13 years after PMV. At the time of PMV, 142 (43.3%) patients had no AR, 124 (37.9%) had mild AR, and 61 (18.7%) had moderate AR. After PMV, the follow-up showed that 120 (36.6%) patients had no AR, 103 (31.5%) had mild AR, and 104 (31.8%) had moderate AR. RESULTS: AR progression after PMV and during the follow-up was significant (P < 0.00), but there was no significant increase in aortic valve replacement (AVR) procedures. The rate of AVR was higher in the moderate AR group (3.8%). There were no significant changes in the left atrial size (LA) (P = 0.6), ejection fraction (EF) (P = 0.4), and rhythm (P = 0.4) before and after PMV, respectively. CONCLUSIONS: Our findings indicate that among patients with rheumatic mitral stenosis, a considerable number have concurrent AR. Concomitant AR at the time of PMV does not influence procedural success and is not associated with inferior outcomes. Rheumatic aortic insufficiency progresses slowly by nature, and patients with AR and mitral stenosis can safely tolerate PMV without the possibility of undergoing AVR in the near future. Patients with moderate degrees of AR remain good candidates for PMV.